OPTIMAL REACTIVE POWER FLOW SOLUTION OF 400-132 KV ELECTRIC NETWORKS OF IRAQ IN THE SOFTWARE PACKAGE RastrWin3 - A. Hussein; M. Zhukov; Y. Kononov (Вестник Северо-Кавказского федерального университета)
In order to reduce energy losses in Iraq's networks with a voltage of 400-132 kV, simulation of modes and optimization of voltage and reactive power in the RastrWin3 software package were performed according to the data of the SCADA. As a result of optimization of the maximum load flow, the total active power losses decreased by 12,7 % - from 517 to 451 MW, and of the minimum load flow by 7,04 % - from 229.7 to 213.5 MW, which corresponds to an annual reduction in energy losses by 385 million kWh or annual savings of 21 million US dollars. It is shown that the main effect is achieved by reducing losses in 132 kV lines. It is established that the network Q/V optimization module in the RastrWin3 does not take into account the change in transformer no-load losses and corona losses in overhead lines in the optimized function, which requires additional research to study their impact on optimization results.